Identification of SARS-CoV-2 E Channel Blockers from a Repurposed Drug Library - Prabhat Pratap Singh Tomar; Miriam Krugliak; Isaiah T. Arkin (MDPI AG, 2021)
SARS-CoV-2, the etiological agent of the COVID-19 pandemic, is a member of the Coronaviridae family. It is an enveloped virus with ion channels in its membrane, the most characterized of which is the E protein. Therefore, in an attempt to identify blockers of the E channel, we screened a library of 2839 approved-for-human-use drugs. Our approach yielded eight compounds that exhibited appreciable activity in three bacteria-based channel assays. Considering the fact that the E channel is the most conserved of all SARS-CoV-2 proteins, any inhibitor of its activity may provide an option to curb the viral spread. In addition, inhibitors can also enhance our ability to understand the exact role played by the E protein during the infectivity cycle. Finally, detailed electrophysiological analyses, alongside in vitro and in vivo studies will be needed to establish the exact potential of each of the blockers identified in our study.